USE OF OIL PALM SHELL AS STRUCTURAL TOPPING FOR SEMI-PRECAST CONCRETE SLAB - Doh, S.I. (CREAM, CIDB Malaysia, 2008)
ABSTRACT Conventional coarse aggregate namely sandstone was used as coarse aggregate for the bottom layer of concrete in the semi-precast slab, while coarse aggregates such as granite, sandstone and OPS were used for the cast-in-situ top layer of concrete. The thickness of bottom and top layers were 50 mm and 75 mm respectively. Six slabs with different toppings were cast and tested. Data presented include the characteristics of deflection and cracking behaviour. The results showed that the semi-precast slab with topping of OPS concrete deflected about 30% more than similar slabs with toppings of granite concrete and sandstone concrete. The investigation also revealed that the type of topping did not affect the strength of the slab significantly. The flexural behaviour of all the three types of semi-precast slabs complied with the requirements specified by the current Codes of Practice (BS8110). Semi-precast slab with the topping of OPS concrete has an added advantage that it is lightweight, thereby reducing the cost of construction. Keywords: OPS, concrete, semi- precast, experimental analysis